Perbandingan Morfometrik Buah Padi Di Kecamatan Pulau Rimau Kabupaten Banyuasin - Dewi Rosanti; Trimin Kartika; Syamsul Rizal; Tedy Sigit Purwansyah (Universitas PGRI Palembang, 2022)
The research to analysis the morphometric of rice fruit was carried out till April to November 2021, with the aim of studying the morphometric of rice fruit planted in community in Pulau Rimau District, Banyuasin Regency. Sampling was done by purposive on one plot in each area of rice varieties. Parameters observed in this study include the morphometric of rice fruit from 8 varieties, namely Inpari 32 HDB, Black Ketan, Cimelati, Ciasem, IR 42, Ciherang, IR 64 and Mapan 05. Morphometric was carried out by measuring the length and diameter of the fruit using a caliper with a caliper. clamping the ends of each rice variety, the width (diameter) was measured using a caliper at the center of the fruit for each rice variety on 50 rice plants per variety. The weight was weighed using an analytical balance. The results showed that structure of fruit are slender, long to short and medium slender. Fruit colours are yellow to grayish black, with diameter of 25 - 28 mm, an length of 7.9 - 10.3 mm, and weight is 1.11 - 1.49 grams